Seed Development in Groundnut - Floral Biology and Peg Development - PC NAUTIYAL (Seed Research, 2026)
Groundnut (Arachis hypogeae L.) is a semi-determinate plant in which flowering continues for a long period depending on the habit group or botanical types. The inflorescence varies among different types, whereas, flower is typically papilionaceous, zygomorphic and self-pollinating (clestogamous). Since, groundnut possesses a geocarpicovary, understanding the physiology of flowering, peg and pod development are important for planning seed production. The inheritance of flower on main stem inflorescence is regulated by two sets of duplicate loci with epistatic action, while sequential flowering is regulated by duplicate pair of recessive genes (i.e., monogenicrecessive to alternate). In Spanish type, flower appears relatively early and has a broader first flowering peak, whereas, in Virginia type flowering is delayed with multiple peaks. Floral induction is controlled by both external as well as internal stimuli and regulates the development of reproductive primordia. The most sensitive stage for induction of flowering is reported to be around three days prior to bloom. Further, the onset of flowering including peg/pod development is controlled by intricate genetic network in response to extrinsic factors, i.e., day length, temperature and intrinsic factors, i.e., hormones, and cross-talks between them, including involvement of endogenous signaling molecules. In addition, groundnut peg has the ability to suspend its development during the period of soil moisture-deficit and resume pod development after the relief of stress. The geotropic nature of peg has a peculiar physiology to fulfill the requirement of darkness for the development of fertilized ovule into pod and seed. For this purpose the peg, along with the fertilized ovary carried at the tip, penetrates the soil under optimum moisture condition. In addition, variation in pod number in groundnut is mainly associated with timing of flowering and the initial rate of flower production. It is a well- established fact that extended exposure to high temperature and water-deficit conditions could reduce flowering and peg numbers as well as pod formation, thus limiting the reproductive efficiency. Such flowering behavior in groundnut results variations in maturity of pod/seed leading to seeds of different size and weight at the final harvest, and resulting in poor quality. Hence, understanding the environmental influence on floral biology and peg development is important for quality seed production in groundnut.